Differential carbonization-shrinkage induced hierarchically rough PAN/PDMS nanofiber composite membrane for robust multimodal superhydrophobic applications - Adnan Ahmad; Hasan Albargi; Mumtaz Ali; Misbah Batool; Ahsan Nazir; Muhammad Bilal Qadir; Zubair Khaliq; Salman Noshear Arshad; Mohammed Jalalah; Farid A. Harraz (Journal of Science: Advanced Materials and Devices, 2023)
Inducing roughness to achieve superhydrophobic surfaces through nanoparticlesʹ inclusion is a well-known concept; however, the consistency and secondary pollutants are challenges to be addressed. As a potential solution, we proposed a superhydrophobic nanofibrous membrane through the electrospinning of polyacrylonitrile and hydrophobic polydimethylsiloxane (PAN/H-PDMS) blended solution and post-heat treatment process. During carbonization, a drastic differential shrinkage between PAN and H-PDMS induces a hierarchically nanorough surface of the electrospun nanofiber. Thanks to the synergistic combination of micro-nano scale hierarchical roughness, a significant improvement in superhydrophobicity was observed with the water contact angle (WCA) of 163.48° and sliding angle (SA) of 4.2°. The proposed composite superhydrophobic nanofibrous membrane (CSN-M) exhibited excellent robustness against the tape peel, abrasion, and bending cycles by maintaining WCA higher than 158° and SA less than 6.5°. The outstanding self-healing feature recovered the WCA to 162.25° and lowered the SA to 5.0° after heat treatment at 60 °C. In addition, the CSN-M revealed a tensile modulus of 12.11 Mpa, a hydrostatic pressure of 39.18 cmH2O, and excellent breathability. The developed CSN-M is strong, with high permeability and outstanding mechano-chemical durability, making it a suitable choice for water/oil separation and self-cleaning applications.